Cannadicas A and B: two new oligosaccharide esters from the roots of Canna indica L. Issue 14 (15th July 2022) - Anh, Luu The; Hieu, Nguyen; Trang, Do Thi; Tai, Bui Huu; Nhiem, Nguyen Xuan; Kiem, Phan Van
Abstract: Two new sucrose derivatives, named as cannadica A (1 ) and cannadica B (2 ), and eight known compounds, 6′- O -acetyl-3- O -( E )- p -coumaroylsucrose (3 ), heterophylloside C (4 ), 6′- O -vanilloylarbutin (5 ), isotachioside (6 ), 2, 6-dimethoxy- p -hydroquinone 1-O-β-D-glucopyranoside (7 ), 3, 5-dimethoxy- p -hydroquinone 1-O-β-D-glucopyranoside (8 ), benzyl glucoside (9 ), and 3, 4-dihydroxybenzaldehyde (10 ) were isolated from the roots of Canna indica L. by various chromatographic methods. Their structures were established by extensive spectroscopic analysis (UV, IR, HR-ESI-MS and NMR) and by comparison of the spectral data with those reported in the literature. Compounds 1 -10 were evaluated their antioxidant activity by peroxyl radical absorbance capacity assay. Compounds 4 and 5 exhibited the most peroxyl radical absorbance capacity. At concentration of 1 µM, their ORACROO* values were 4.86 ± 0.39 and 3.11 ± 0.26, respectively, fold-up to that of trolox as an internal standard. Graphical Abstract: UF0001